(untitled) (African Journal of Biomedical Research, 2024)
A systematic review of the literature was conducted to describe the available data on adolescent contraceptive usage. The keywords used in the search include: adolescent, contraceptive use, contraceptives, adolescent reproductive health disease in PUBMED, MEDLINE, CINAHL Plus, Nursing and Allied Health, and SAGE, which resulted in a total of 452 published papers. The researcher ensured that the articles/journals were materials of high quality which satisfied the following characteristics of inclusion such as; there was a title for each paper, the name(s) of the author(s) was/were clearly written on the papers, the paper must have been published between the years 2014 and 2022 and the paper must be available in academic search tools and databases, published by official and credible sources. A total of 13 relevant journal articles were believed to be suitable for inclusion by the researcher in the systematic review.